Association of telephone follow-up–based prescription proposals initiated by community pharmacists with oncology-related professional certification on quality of life of cancer patients receiving outpatient chemotherapy: a single-center observational study - Toshiki Nakamura; Kazunori Tamegai; Takeshi Sakamoto; Michinori Sakai; Masahiko Kimura; Takeshi Hirayama (Journal of Pharmaceutical Health Care and Sciences, 2026)
Abstract Background The association of prescription proposal after telephone follow up (TFU) initiated by health insurance-covered pharmacy-based pharmacists (hereinafter “community pharmacists”) having oncology-related professional certification with patients’ quality of life (QOL) has not been elucidated. This study investigated changes in QOL before and after prescription proposals following TFUs in cancer patients receiving outpatient chemotherapy. Methods Cancer patients undergoing outpatient chemotherapy, who used Akebono Pharmacy Medical Branch and received TFU between August 2023 and July 2025 were analyzed. Follow-up was conducted using a Telephone Follow-up Form. Adverse events were assessed through open-ended questions, and severity was graded based on the Common Terminology Criteria for Adverse Events. QOL was assessed using the European Quality of Life Five Dimensions Five Levels (EQ-5D-5L) scale. Results Among 107 community pharmacist-initiated prescription proposals, 84 resulted in prescription changes, and QOL improved significantly after prescription changes (p < 0.001). By adverse event type, the severity (grade) of pain, nausea, and constipation was also mitigated significantly after prescription changes (p < 0.001, p = 0.002, p = 0.037, respectively). Discussion This study suggests that community pharmacist-initiated prescription proposals based on TFU may contribute to favorable QOL outcomes through mitigating adverse events in cancer patients undergoing outpatient chemotherapy. However, some patients showed QOL improvement even though the adverse event grade remained unchanged. These results suggest that QOL assessment using the EQ-5D-5L in cancer patients undergoing outpatient chemotherapy may complement adverse event grades by capturing changes in patients' subjective health status.